Carbon Microspheres with Cr(VI) Adsorption Performance were Prepared by In-situ Hydrothermal Carbonization Method - Shaojie Chen; Xinzhuo Wu; Mei Li; Yuhan Xu; Zihao Yuan; Zhao Li; Jing Li (Bulletin of Chemical Reaction Engineering & Catalysis, 2023)
Biochar material is a renewable adsorbent widely used for treating contaminated wastewater. The hydrothermal carbon (HTC) were prepared from low polymeric sugars and low concentration glucose under hydrothermal carbonization reactions without using dispersants. The composition and structure of the biochar produced were characterized using X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), Raman spectroscopy (Raman), and N2 adsorption-desorption, indicating that amorphous graphitic carbon was obtained. Experimental results from the static adsorption of Cr(VI)-contaminated wastewater showed that HTCP-2 exhibited the highest adsorption capacity for Cr(VI), with a maximum adsorption capacity of 22.62 mg.g−1.The adsorption Cr(VI), MB, and RhB by the synthesized biochar all conformed to the pseudo-second-order kinetic model and Freundlich isotherm, suggesting a multilayer chemical adsorption process. Additionally, the synthesized HTC surface is enriched with a significant amount of oxygen-rich functional groups, which also has good adsorption performance for cationic dyes. Furthermore, the test results of fluorescence, photocurrent, and impedance indicate that HTCP-2 possesses the ability to generate and separate photoinduced charge carriers. This implied that HTCP-2 can be used for the preparation of adsorption photocatalysts, which effectively remove environmental pollutants through the synergistic effect of adsorption-photocatalysis. This study provides a research foundation for advancing water treatment technologies. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).